Expression of microRNA let-7a positively correlates with hepatitis B virus replication in hepatocellular carcinoma tissues. Issue 9 (May 2017) - Qiu, Dongni; Chen, Jian; Liu, Jie; Luo, Zhongguang; Jiang, Weiru; Huang, Jianping; Qiu, Zhibing; Yue, Wenjie; Wu, Lijun
Let-7a miRNA is downregulated in various cancers. However, in hepatocellular carcinoma (HCC) patients infected with hepatitis B virus (HBV), the relationship between let-7a and HBV replication has not been fully elucidated. Liver specimens were collected from 23 HCC patients with chronically active HBV. The serum levels of the HBV antigens hepatitis B surface antigen (HBsAg) and hepatitis B virus e antigen (HBeAg), and the HBV antibodies, anti-HBs, anti-HBe and anti-hepatitis B core antigen (anti-HBc) were measured using the microparticle enzyme immunoassay. Let-7a levels and HBV DNA copy numbers were measured by quantitative real-time PCR (qRT-PCR) and analyzed statistically. A let-7a specific antisense oligonucleotide was introduced to the HBV-producing cell line HepG2.2.15 and a change in HBV DNA copy numbers was assessed by qRT-PCR. HCC patients with highly active HBV replication (>10 6 DNA copies/mL) showed higher levels of serum HBsAg and anti-HBc than patients with less active HBV replication (<10 3 DNA copies/mL). The level of let-7a was lower in malignant tissues than in adjacent normal tissues. However, patients with highly active HBV replication demonstrated a significantly higher level of let-7a in hepatocarcinoma tissue than patients with less active HBV replication ( P  < 0.05). A higher level of let-7a was observed in the HBV-producing cell line HepG2.2.15 than in HepG2 cells ( P  < 0.05), and let-7a down-regulation by antisense oligonucleotides led to a reduction in HBV DNA copy numbers ( P  < 0.05), indicating a correlation between the let-7a level and HBV replication. Down-regulation of let-7a reduces HBV replication and could prevent the development of HCC, suggesting it could be an effective therapeutic treatment for HBV infection. Impact statement: Although interferon and nucleic acid analogues effectively suppress HBV replication in HBV patients, there is no treatment which eradicates the virus. Moreover, the therapeutic effect can be reduced by virus mutations or drug resistance. Let-7a is a miRNA initially found in the nematode as a master regulator of developmental processes, but also exists in humans. It has been reported that the transcription of let-7a was much lower in HCC than in normal liver tissues and specific miRNA could directly promote virus replication. Therefore we hypothesized that transcription of let-7a promotes HBV replication, which might compromise the therapeutic effects of antivirus treatments. In our present study, we demonstrated a correlation between let-7a transcription and HBV replication in surgical specimens obtained from patients with HCC, as well as in HCC cell lines. Our finding might be the base for a new approach to improve HBV infection treatments in the future.